1992
DOI: 10.1177/019262339202000301
|View full text |Cite
|
Sign up to set email alerts
|

Renal Transplacental Carcinogenicity of 3,3-Dimethyl-1-Phenyltriazene in Rats: Relationship of Renal Mesenchymal Tumor to Congenital Mesoblastic Nephroma and Intralobar Nephrogenic Rests

Abstract: Exposure of rat embryos to 3,3-dimethyl-1-phenyltriazene (DMPT) results in numerous malformations, but the urogenital system is not affected. In contrast, exposure of rat fetuses to DMPT has been reported to result in renal neoplasms, which were not further classified. To better understand this discrepancy in organotropism of the teratogenic and transplacental carcinogenic processes, the present study was undertaken to characterize the neoplasms induced in rat fetuses exposed to DMPT in utero. Renal neoplasms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…In this preliminary study, a single injection of 50 mg/kg MNU given to Lewis rats at birth induced a high incidence of mortality and mammary cancers with severe hematotoxicity. Rats are most sensitive to the induction of renal tumors when alkylating agents are administered at the early weeks after birth, when the rate of cell division in the immature kidney is the highest (10,22). Like this experimental protocol, a short-term study (60 days) with 35 mg/kg MNU as a non-lethal lower dose without the incidence of mammary cancers, may therefore be extremely useful for testing the promotion, progression or inhibitory effects of chemical and physical agents on cell proliferation and transformation in rat kidneys.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this preliminary study, a single injection of 50 mg/kg MNU given to Lewis rats at birth induced a high incidence of mortality and mammary cancers with severe hematotoxicity. Rats are most sensitive to the induction of renal tumors when alkylating agents are administered at the early weeks after birth, when the rate of cell division in the immature kidney is the highest (10,22). Like this experimental protocol, a short-term study (60 days) with 35 mg/kg MNU as a non-lethal lower dose without the incidence of mammary cancers, may therefore be extremely useful for testing the promotion, progression or inhibitory effects of chemical and physical agents on cell proliferation and transformation in rat kidneys.…”
Section: Resultsmentioning
confidence: 99%
“…It is characterized by discrete clusters of highly basophilic blast cells surrounding mature ducts and organoid differentiation as epithelial rosettes, primitive basophilic tubules, attempted glomerulus formation or mature epithelial ducts (20,21). Nephroblastomatosis is a small, solitary, basophilic cell mass consisting of densely crowded blast cells with ill-defined cytoplasm and basophilic nuclei and a few signs of early organoid differentiation into epithelial rosettes (20,22,23). Nephroblastomatosis has the potential to develop into a nephroblastoma as it grows, and is regarded as a preneoplastic lesion of nephroblastoma (24).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example of chemical induction, Stoica and Koestner 20 reported that a single high dose (180 mg/kg) of intraperitoneal ENU caused ameloblastic odontoma in 30-day-old male rats. Moreover, Frank et al 8 described that odontomas in the dentitious tissue occurred in 3/18 male SD rats following a transplacental exposure to 3,3-dimethyl-1-phenyltriazene on days 16, 18, and 20 of gestation. No data are available on ameloblastic odontoma with ENU in other species, though methylnitrosourea caused this tumor in Syrian golden hamsters 23 .…”
Section: Discussionmentioning
confidence: 99%
“…These anatomic locations of perilobar and intralobar can also be applicable to the rat kidney, which is unipyramidal in nature. Superficial cortical areas in the rat kidney are perilobar, and the corticomedullary region are intralobar (Frank et al 1992). Intralobar nephroblastematosis (ILNB) is a precursor lesion to the development of NB in rats.…”
Section: Introductionmentioning
confidence: 99%